The kaleidoscopic midwife: a conceptual metaphor illustrating first-time mothers' perspectives of a good midwife during childbirth. A grounded theory study - Borrelli, Sara E.; Spiby, Helen; Walsh, Denis (Elsevier, 2016)
Background: The literature review reveals general information about a good midwife from a range of perspectives and what childbearing women generally value in a midwife, but there is a lack of information around mothers’ perspectives of what makes a good midwife specifically during labour and birth, and even less in the context of different places of birth.